RESEARCH OF THE INFLUENCE OF ADDING ROTTEN WOOD ON THE MECHANICAL QUALITY OF PELLETS (Innovation in Woodworking Industry and Engineering design, 2026)
This paper analyzes the effect of adding wood attacked by brown rot fungi to basic wood raw material with the aim of increasing the mechanical strength of wood pellets. Wood attacked by brown rot fungi has an increased share of lignin which is natural glue and can contribute to better mechanical properties of wood pellets. Wood pellets were produced on a single pellet press and pressed with adjusted production parameters at two different temperatures. Produced pellets were tested on some mechanical and physical properties. The analysis of experimental results has shown the statistical significant improvement of the mechanical properties of pellets by adding brown rot fungi wood.